Othello - Shakespeare, William, 1564-1616; Wieland, Christoph Martin, 1733-1813 (Salt Lake City, UT : Project Gutenberg, 2004)
"Othello" by William Shakespeare is a tragedy written around 1603. Set in Venice and Cyprus, the play follows Moorish military commander Othello as his ensign Iago manipulates him into suspecting his wife Desdemona of infidelity. Through cunning deception and planted evidence, Iago exploits Othello's trust and preys on his insecurities, setting in motion a devastating chain of events. Considered one of Shakespeare's greatest tragedies, the play explores themes of jealousy, manipulation, and race through its demanding central roles. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Othello
Release date is 2004-12-01
Produced by Delphine Lettau
Keywords: Tragedies (Drama); Othello (Fictitious character) -- Drama; Jealousy -- Drama; Interracial marriage -- Drama; Venice (Italy) -- Drama; Muslims -- Drama